The impact of strategic management on business outcomes: Empirical research - Tone Ceésnovar (Journal for East European Management Studies, 2006)
Strategic management originates from strategic planning and as a technique for managing all important aspects of a company's environment it scientifically differs from other management techniques that only seek to improve operational effectiveness. Therefore, the empirical research first aimed to determine the influence of systematic use of strategic management, which fits in with prescriptive schools, on Slovenian wood-processing companies' business outcomes. The second aim was to establish the characteristics of using strategic management in order to improve a company's competitiveness. The empirical research reveals that those companies systematically applying strategic management achieved better business results than those that did not. To achieve a better effect in the use of strategic management, companies should improve in the preparing and assessing phases of using it. – – Strategisches Management entsteht aus der strategischen Planung. Als eine Technik, die alle wichtigen Aspekte der Unternehmensumgebung in die Analyse einbezieht, unterscheidet sie sich signifikant von anderen Management- Techniken, die nur eine Optimierung des operativen Ergebnisses im Fokus haben. Folglich zielte die empirische Forschung zuerst darauf ab, den Einfluß des systematischen Gebrauchs von strategischem Management, wie er durch die führenden Schulen vorgegeben wird, auf die Geschäftsergebnisse slowenischer Unternehmen der Holzverarbeitung festzustellen. Das zweite Ziel war, die Eigenschaften des verwendeten strategischen Managements, das die Wettbewerbsfähigkeit der Firma verbessern sollte, heraus zu arbeiten. Die empirische Forschung deckt auf, dass jene Firmen, die systematisch strategisches Management anwenden, bessere Geschäftsresultate erzielten als die, die das nicht taten. Um beim strategischen Management einen größeren Erfolg zu erzielen, sollten Unternehmen schon in der Vorbereitung und beim Festsetzen der einzelnen Phasen Gebrauch davon machen.
Keywords: 650; management technique; strategic management; business outcomes; financial indicators; company